Legal Implications on Social and Educational Activities Regarding the Change in The Position of Foundations in Law Number 28 of 2004 - Aji, Ahmad Mukri; Yunus, Nur Rohim; Mukri, Syarifah Gustiawati (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
This study examines the legal implications of changes to the status of foundations as outlined in Law No. 28 of 2004, specifically regarding their social and educational activities in Indonesia. The purpose of this study is to analyse how changes in the status of foundations as legal entities affect their management, and to identify solutions that can optimise the role of foundations in the social and educational fields. This study employs a qualitative research method, incorporating a literature-based approach and legal analysis. Data were obtained from various sources, including scientific journals, legal literature, and relevant laws and regulations, which were analysed using a normative legal approach. The results of the study indicate that the changes regulated in Law No. 28 of 2004 provide a more substantial legal basis for foundations to carry out social and educational activities more accountably and transparently. However, there are challenges related to the management and supervision of foundations that must be faced, including the potential for abuse of authority by foundation administrators. This study suggests the need for strengthening regulations, more effective supervision, and the application of sound corporate governance principles to ensure that foundations play a maximum role in social and educational activities.Keywords: Legal Implications; Foundations; Social and Educational Activities: Changes in the Status of Foundations